Decentralization and Regionalization of Surgical Care as a Critical Scale-up Strategy in Low- and Middle-Income Countries; Comment on "Decentralization and Regionalization of Surgical Care: A Review of Evidence for the Optimal Distribution of Surgical Services in Low- and Middle-Income Countries" - Jaymie A. Henry (Kerman University of Medical Sciences, 2021)
As global attention to improve the quality, safety and access to surgical care in low- and middle-income countries (LMICs) increases, the need for evidence-based strategies to reliably scale-up the quality and quantity of surgical services becomes ever more pertinent. Iversen et al discuss the optimal distribution of surgical services, whether through decentralization or regionalization, and propose a strategy that utilizes the dimensions of acuity, complexity and prevalence of surgical conditions to inform national priorities. Proposed expansion of this strategy to encompass levels of scale-up prioritization is discussed in this commentary. The decentralization of emergency obstetric services in LMICs shows promising results and should be further explored. The dearth of evidence of regionalization in LMICs, on the other hand, limits extrapolation of lessons learned. Nevertheless, principles from the successful regionalization of certain services such as trauma care in high-income countries (HICs) can be adapted to LMIC settings and can provide the backbone for innovation in service delivery and safety.